Institutional Evaluation in Improving Student Literacy Through the Implementation of the Merdeka Curriculum - Sheptian, Riky; Soeprijanto, Soeprijanto; Riyadi, Riyadi; Badrujaman, Aip (Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
Literacy is essential for academic success, social engagement, and long-term career prospects. This study analyzes literacy improvements under the Independent Curriculum from 2023 to 2025 using the Education Report Card. The analysis evaluates the curriculum's impact on literacy, readiness for high school, and the role of literacy in social engagement. The study used a longitudinal approach, collecting education reports, teacher and student interviews, and annual surveys. This provided a comprehensive view of literacy development. Results showed significant improvement during the study. By 2025, all students will have achieved minimum literacy competencies, and 73.68% exceeded the standards. The findings highlight the value of collaborative projects, such as fake news analysis and gender equality campaigns, in strengthening text evaluation and critical thinking. However, challenges remain, including limited funding for technology and achievement disparities. The study emphasizes the need for coordination between curriculum policies, teacher training, and inclusive learning environments to maintain literacy gains. The findings should help policymakers and educators design effective and sustainable literacy strategies to meet future educational demands.